Implementation of STEM-Based Learning Modules Containing Islamic Values to Improve Student Learning Outcomes and Motivation - Putri Raisah; Hafnati Rahmatan; Rini Safitri (Jurnal Penelitian Pendidikan IPA, 2023)
Student learning motivation is the main aspect in achieving student success. Based on the results of observations and interviews, student learning motivation at MTsN 8 Pidie and MTsN 11 Pidie is still relatively low, which has an impact on low student learning outcomes. The aim of this research is to determine the difference in increasing student learning outcomes and motivation on respiratory system material after implementing a STEM-based learning module containing Islamic values. The population of this study were all students in class VIII MTsN 8 Pidie and MTsN 11 Pidie. The samples were taken by purposive sampling, at MTsN 8 Pidie the research samples were class VIII.1 and class VIII.2. Meanwhile at MTsN 11 Pidie the research samples were class VIII.2 and class VIII.3. Data collection uses questionnaire instruments to measure learning motivation and uses test question instruments to measure student learning outcomes. The results of data analysis using a test (Mann-Whitney test) show that there are differences in motivation and learning outcomes, namely a significant value of 0.000 < 0.05, meaning that there is a significant difference between the motivation and learning outcomes of control class and experimental class students. Therefore, it can be concluded that there is an increase in learning outcomes and student motivation by implementing STEM-based modules with Islamic values